Level Of Awareness Of ISO 9001:2015 QMS And Process Owners’ Work Motivation (Journal of Namibian Studies : History Politics Culture, 2023)
The study aimed to ascertain the level of awareness ISO 900:2015 Quality Management System (QMS) and process owners’ work motivation of Bohol Island State University.  Specifically, it is directed to: 1. determine the profile of the respondents in terms of: age, sex, highest educational attainment, position/designation, number of years in the position, and number of related QMS trainings, seminars, workshops and conferences attended; 2. assess the level of awareness of ISO 9001:2015 Quality Management System of the university in terms of context of the organization, leadership, planning, support, operation, performance evaluation, and improvement; and 3. determine the significant relationship between profile of the respondents and the level of awareness of ISO 9001:2015 quality management system of the university and the process owners’ work motivation. This study employed descriptive survey design comprising the six different campuses of BISU as the locale with three hundred thirty-two (332) process owners as respondents. The study utilized Chi-Square test using R software. Findings revealed that process owners were very well-informed to the major requirements of the QMS in the University, except clause 6, planning; clause 7, support and clause 8, operation. In addition, notwithstanding additional work loads, process owners were highly motivated.  Moreover, the study concludes that their sex, educational attainment, position/designation, and number of relevant trainings/seminars/workshops attended are contributing factors to their level of awareness of ISO 9001:2015 QMS. Likewise, full awareness of the standards can increase work motivation among employees in the University’s compliance to ISO 9001:2015 QMS.